Pengembangan Media Kartu kata Bergambar Untuk Meningkatkan Keterampilan Membaca Permulaan Pada Siswa Kelas 1 SD Inpres Bertingkat Kelapa Lima 2 Kota Kupang - Yohana Baeama; Konradus S Jenahut; Angelina C.O.R. Lake; Rince S.M Benu (STKIP Subang, 2025)
This research and development was motivated by a problem found at SD Inpres Bertingkat Kelapa Lima 2, Kupang City. This problem is characterized by students' suboptimal beginning reading skills, particularly in memorizing and recognizing letters of the alphabet, which hinders their learning in class. Therefore, media such as picture word cards are needed to assist students in learning beginning reading, to attract their attention and interest. This study aims to develop effective picture word cards to improve beginning reading skills in grade I students of SD Inpres Bertingkat Kelapa Lima 2, Kupang City. This study used the research and development method with the ADDIE model: Analysis, Design, Development, Implementation, and Evaluation. The subjects were first-grade students at SD Inpres Bertingkat Kelapa Lima 2, Kupang City. The media development consisted of picture word cards, created based on the steps and tailored to students' learning needs. The quality of the picture word cards was assessed by expert validators, teacher responses, and student responses. The validation test results for the picture word cards by material experts and media experts categorized them as very valid, with validity scores of 95 and 90, respectively. The results of the teacher and student response tests for the picture word cards categorized them as very good (SB) with percentages of 87.5% and 83.3%, respectively. Based on the expert validation data, teacher responses, and student responses, it can be concluded that the picture word cards developed for beginning reading material are suitable for use as a medium in the learning process.